PENGARUH PEMANFAATAN FASILITAS WI-FI TERHADAPSIKAP BELAJAR MAHASISWA DAN KONTRIBUSINYA TERHADAP INDEKS PRESTASI MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK ELEKTRONIKA UNIVERSITAS NEGERI PADANG - Renol Fitria Asdi; Almasri Almasri; Sukaya Sukaya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2016)
The background of this research problem is not the maximum grade students of Electronics Engineering Education UNP. This research is a correlational study. The research objective is to reveal how much contribution the use of Wi-Fi and students' attitudes toward student achievement index. The study population numbered 337 people and the sample amounted to 72 students Prodi Electronics Engineering Education at the Department of Electronics Engineering FT-UNP. The sampling technique is done nonprobability Sampling Design withdrawal technique is by incidental sampling technique. Data on student achievement index obtained from students Prodi Electronics Engineering Education at the Department of Electronics Engineering FT-UNP. While data Utilization Wi-Fi facilities and students' learning attitudes collected through questionnaires distributed to students by using a Likert scale has been tested for validity and reliability. The result showed that (1) the use of facilities WI-Fi Influential significantly influence the attitude of students' study program Engineering Education Elktronika UNP 11.32%, (2) use of WI-Fi facilities contribute significantly to the achievement index of Technical Education Study Program UNP Elktronika of 15.14%, (3) the attitude of student learning contribute significantly to the achievement index mahsiswa Education Study program Electrical Engineering UNP by 20.07%. So it can be concluded that the use of the facilities WI-Fi and Attitude of Student Learning Contribute to the achievement index mahsiswa Engineering Education Study program Elktronika UNP, the increasing use of Wi-Fi and the higher the students' learning attitude, the higher the grade the student%. KeyWord :       students motivation, management of the class by the teacher, learning outcomes.